Clinical Implication of Dosimetry of Computed Tomography- and Fluoroscopy-Guided Intrathecal Therapy With Nusinersen in Adult Patients With Spinal Muscular Atrophy - Kizina, Kathrin; Stolte, Benjamin; Totzeck, Andreas; Bolz, Saskia; Fleischer, Michael; Mönninghoff, Christoph; Guberina, Nika; Oldenburg, Denise; Forsting, Michael; Kleinschnitz, Christoph; Hagenacker, Tim (Frontiers in Neurology, 2019)
Background Spinal muscular atrophy (SMA) is a genetic disorder that leads to progressive tetraparesis. Nusinersen is the first approved drug for the treatment of SMA and is administered via intrathecal injections. Neuromyopathic scoliosis and spondylodesis can impede lumbar punctures, thus necessitating the use of radiological imaging. Furthermore, dosimetry of this potentially lifelong therapy should be supervised. Methods Fluoroscopy-assisted or computed tomography (CT)-guided intrathecal injections of nusinersen were performed in adult patients with SMA type 2 and 3. The mean effective dose was compared in patients with and without spondylodesis as well as in those with SMA type 2 and 3. The dosimetry was analyzed in relation to the motor function evaluated with the Revised Upper Limb module (RULM) score and the Hammersmith Functional Motor Scale-Expanded (HFMSE) score. Results Fifteen patients with SMA type 2 and 3 underwent radiological imaging-assisted intrathecal injections. The mean effective dose per CT-guided injection per patient was 2.59 (± 1.67) mSv (n=12). The mean dose area product (DAP) per fluoroscopy-guided injection per patient was 200.48 (± 323.67) µGym2 (n=3). With increase in the number of injections, the effective dose (r = -0.23) (p < 0.05) and the DAP (r = -0.09) (p > 0.05) decreased. The mean effective dose in 4 patients without spinal fusion (SMA type 2) was 1.39 (± 0.51) mSv, whereas that in 8 patients with spondylodesis (SMA type 2 and 3) was 3.21 (± 1.73) mSv. The mean effective dose in 5 SMA type 2 patients with spondylodesis was 2.68 (± 1.47) mSv (n=5) and in 3 SMA type 3 patients was 4.00 (±1.82) mSv. Dosimetry did not show significant correlation with the clinical severity of the disease (RULM score: r = -0.045, p > 0,05 and HFMSE score: r = -0,001, p > 0,05). Conclusions In SMA type 2 and 3 patients undergoing radiological imaging-assisted injections, the effective dose and DAP decreased during therapy with nusinersen. The mean effective dose in patients with spondylodesis was higher than that in patients without spondylodesis. Dosimetry should be monitored carefully in order to detect and prevent unnecessary radiation exposure.